2022
DOI: 10.1002/ijc.33943
|View full text |Cite
|
Sign up to set email alerts
|

A serum lipidomics study for the identification of specific biomarkers for endometrial polyps to distinguish them from endometrial cancer or hyperplasia

Abstract: Endometrial diseases, including endometrial polyps (EP), endometrial cancer (EC) and endometrial hyperplasia (EH), are common gynecological diseases that affect women of childbearing and perimenopausal age. Clinically, biopsy or imaging methods are usually used to screen and diagnose these diseases; however, due to the invasiveness and heterogeneity of these tests, a noninvasive, convenient, objective and accurate biomarker is needed for the differential diagnosis of EP, EC or EH. In the present study, serum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…To ensure data quality in the lipidomic analysis, we analyzed the samples randomly and prepared mixed QC samples by mixing 10 μL of supernatant from each sample. The QC samples were inserted uniformly into each set of analytical run sequences for the methodology validation of the large-scale metabolomics analysis method . We investigated the precision of the instrument by performing six consecutive injections of the same QC sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure data quality in the lipidomic analysis, we analyzed the samples randomly and prepared mixed QC samples by mixing 10 μL of supernatant from each sample. The QC samples were inserted uniformly into each set of analytical run sequences for the methodology validation of the large-scale metabolomics analysis method . We investigated the precision of the instrument by performing six consecutive injections of the same QC sample.…”
Section: Methodsmentioning
confidence: 99%
“…The QC samples were inserted uniformly into each set of analytical run sequences for the methodology validation of the large-scale metabolomics analysis method. 41 We investigated the precision of the instrument by performing six consecutive injections of the same QC sample. To determine the method repeatability, seven QC samples were parallelly prepared and analyzed consecutively.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of proteomics, four studies only validated their data using independent sample cohorts (104,107,113,119), and one study (115), validated their proteomic-based model in a subsequent publication using TMAs (126). Three metabolomic studies performed similar validations in independent cohorts (138,142,144), and one study in particular successfully validated the metabolic profiles identified in serum samples (136) also using dried blood and reported excellent diagnostic characteristics (144). For validation, the authors adopted a prospective design on a very large study cohort (over 1,000 subjects), therefore, candidate biomarkers identified in this study bear great potential for translation into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…For validation, the authors adopted a prospective design on a very large study cohort (over 1,000 subjects), therefore, candidate biomarkers identified in this study bear great potential for translation into clinical practice. Of interest, these biomarkers include steroids, which were also selected as candidate molecules in other studies (135,157) A caveat in a number of the included studies on proteomics (102, 104, 108) or metabolomics (136,138,142,143) is the use of healthy (not age/comorbidity matched) women, likely resulting in an overestimated diagnostic accuracy. Also, if pre-menopausal controls are included, this may induce biases as EC is predominantly a postmenopausal disease (114-116, 122, 147, 149, 154).…”
Section: Discussionmentioning
confidence: 99%
“… 551 Using a ROC curve and logistic regression analysis, a biomarker panel of PA(37:4), 6-keto-PGF1α, PS(36:0), and LysoPC(20:1) demonstrated good classification and diagnostic ability in distinguishing endometrial polyps from endometrial hyperplasia or endometrial cancer in the validation set. 552 Notably, targeted metabolomics analyses identified gamma-aminobutyric acid markedly reduced in COVID-19 patients and its change levels with high sensitivity that allowed for COVID-19 stratification. 553 …”
Section: Disease Classification and Stratificationmentioning
confidence: 99%